Analisis Keterbacaan Buku English for Nusantara untuk Kelas Tujuh Menggunakan WebFX - Basori (Fakultas Tarbiyah dan Ilmu Keguruan UIN Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2023)
English for Nusantara (EN) books are textbooks provided by the Indonesian government and serve as educational materials that teachers can use to teach and learn English in Indonesia junior high schools. Before using them, teachers must evaluate their readability since inappropriate materials can demotivate students and enable them to achieve teaching and learning goals. This study aimed to fill the gap by evaluating the readability of EN. Using a sample EN for grade seven, this study brought a research question, what is the level of readability of English for Nusantara. To achieve this goal, the researcher used a qualitative study. The researcher used a free online readability tool to measure the text readability level, the WebFX. Among the texts in EN for grade seven, the researcher took 18 texts and analyzed them using the measurement formula in the tools above. The study found that the readability level was high, and the texts were easy to read. The limitations of the study and suggestions for future research were also discussed.